Chronic traumatic encephalopathy: the nature, mechanisms and stages of development - Pedachenko, Eugene G.; Lisianyi, Nikolay I. (Ukrainian Neurosurgical Journal, 2019)
The survey provides data on the history of discovery and the epidemiology of chronic traumatic encephalopathy, which can occur after a single or repeated mild traumatic brain injury. Chronic traumatic encephalopathy has a nearly century-long history and was first identified in boxing veterans. Initially, signs of progressive neurological disease (punch-drunk), which occurred after repeated multiple traumatic brain injury in boxers, were described. Other sport activities alongside with box, associated with repeated mild brain injuries may cause dementia and neurodegenerative diseases. That led to the use of the term “chronic traumatic encephalopathy” (CTE). The features of the disease are defined, namely, that it occurs many years after the injury and develops in very small percentage of persons experienced a head injury, and clinically it resembles such neurodegenerative disorders as Parkinson’s and Alzheimer’s diseases. The paper deals with the pathogenesis associated with the accumulation of beta amyloid, tau protein, the development of neuro-inflammation and immune-associated reactions, including intracerebral local and systemic immune processes. The review indicates the role of genetic susceptibility, resistance to injury, gender, physiological stress, environmental exposure and age in the development of CTE. The significance of immune responses and inflammation in the development of various forms of neurodegenerative diseases and CTE is widely recognized, but the mechanisms of the immunoprotective and immunodegenerative actions are still not well understood and require special experimental studies. The review notes different role of immune responses in the pathogenesis at certain stages of development of CTE. The protective and immunopathological mechanisms of chronic traumatic encephalopathy are analyzed in detail; three main periods of its development have been identified, and new approaches to the study and treatment have been outlined.